Prediction of rockburst intensity grade in deep underground excavation using adaptive boosting classifier - Ahmad, Mahmood; Katman, HerdaYati; Al-Mansob, Ramez; Ahmad, Feezan; Safdar, Muhammad; Alguno, Arnold C. (Wiley-Hindawi, 2022)
Rockburst phenomenon is the primary cause of many fatalities and accidents during deep underground projects constructions. As a result, its prediction at the early design stages plays a significant role in improving safety.(e article describes a newly developed model to predict rockburst intensity grade using Adaptive Boosting (AdaBoost) classifier. A database including 165 rockburst case histories was collected from across the world to achieve a comprehensive representation, in which four key influencing factors such as maximum tangential stress of the excavation boundary, uniaxial compressive strength of rock, tensile rock strength, and elastic energy index were selected as the input variables, and the rockburst intensity grade was selected as the output. (e output of the AdaBoost model is evaluated using statistical parameters including accuracy and Cohen’s kappa index. (e applications for the aforementioned approach for predicting the rockburst intensity grade are compared and discussed. Finally, two real-world applications are used to verify the proposed AdaBoost model. It is found that the prediction results are consistent with the actual conditions of the subsequent construction.